Propuesta de intervención urbana en mercados de la ciudad de Riobamba, caso de estudio mercado la Esperanza 1 y 2 y plaza de las hierbas - Zúñiga Cabezas, José Andrés (2023)
The following thesis has its architectural and urban intervention in the food markets: La Esperanza 1-2 and Plaza de las hierbas, all belonging to Polygon Z30 of the City of Riobamba. Based on research, we have analyzed the role achieved by this commercial equipment and its correlation with the rest of the city. Each studied market has its very own features, from selling products to existing services and infrastructure. To develop both investigation and intervention, we will begin with a general urban analysis based on qualitative and quantitative factors that allow us to identify the existing difficulties, discrepancies, and potentialities in both the markets and the immediate surroundings of the selected polygon. Besides, surveys and interviews are made with all the involved individuals (residents, administrators, sellers, and consumers) that go to these markets better to understand their social influence from different points of view. Throughout an urban renovation, a continuous system of equipment is projected, having as a goal reactivating the selected polygon within the Z30 zone in a peripheral condition through the mystification of the low level, considering multipurpose spaces as strategic points as far as recovering public space, green spaces, and promoting safe zones are concerned